Lack of PI 3-kinase isoform p110alpha in smooth muscle cells impairs aortic wall homoeostasis and thus promotes aortic aneurysm formation. (25th November 2020) - Vantler, M; Berghausen, E; Zierden, M; Mollenhauer, M; Mehrkens, D; Adam, M; Baldus, S; Rosenkranz, S
Abstract: Background: In smooth muscle cells (SMCs), the PI 3-kinase isoform p110α mediates receptor tyrosine kinase dependent proliferation, chemotaxis and cell survival. Since mice, harbouring a smooth muscle specific p110α deficiency (SM-p110α−/−), display reduced vascular wall thickness, we hypothesized that SM-p110α−/− mice might be prone to aortic aneurysm (AA) formation. The pathogenesis of AA is characterized by increased dedifferentiation of SMCs, extracellular matrix (ECM) degeneration and inflammation in the aortic wall. Herein, we investigated how p110α-dependent signal transduction in SMCs affects these processes. Methods and results: We examined AA formation in SM-p110α−/− mice and wild-type littermates using the "porcine pancreatic elastase" (PPE) AA model. PPE was infused into the infrarenal aorta to induce AA formation. Ultrasound examination of the aorta revealed an enlarged aortic diameter in all PPE-treated mice. The aortic diameter in SM-p110α−/− mice (0.46±0.12 mm) was significantly increased compared to wild-type animals (0.18±0.03 mm, p<0.01). These data indicate a protective function of p110α in AA formation. Immunocytochemical examination of the tunica media of PPE-perfused SM-p110α−/− mice revealed significantly increased infiltration of CD45+ leukocytes. In particular, the number of MOMA-2+ monocytes / macrophages in the vessel wall was significantly increased indicating elevated inflammation of the aortic wall during AA progression in comparison to wild-type control mice. Ultrastructural analysis of aortic wall morphology in SM-p110α−/− mice using transmission electron microscopy (TEM) showed a deranged tunica media and increased apoptotic cell death. In addition, the media thickness in the abdominal aorta was significantly reduced in SM-p110α−/− mice (29.0±3.1 μm vs. 42.5±4.1 μm). Western blots demonstrated a reduced elastin and fibrillin expression in SMCs from SM-p110α−/− mice. p110α−/− SMCs showed significantly reduced expression of differentiation markers SM-α-actin and SM-MHC. In addition, aortic p110α-deficient SMCs were significantly impaired in their ability to proliferate and migrate. These findings indicate that p110α−/− SMCs are neither differentiated nor dedifferentiated and have therefore largely lost their plasticity. Consequently, p110α deficiency significantly diminished responsiveness of aortic rings to vasodilator acetylcholine and NO-donor nitroglycerin, further indicating impaired contractility of SMCs. Mechanistically, we demonstrated that PDGF and insulin induced phosphorylation and inactivation of key regulators of SMC differentiation and dedifferentiation, Foxo4 and GSK3b, respectively, were abrogated in p110α−/− SMCs. Conclusion: These data show that deficiency of p110α in SMCs promotes the formation and progression of AA. Causative are impaired SMC plasticity and ECM homeostasis as well as inflammatory processes in the vascular wall. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft (DFG)